Implementasi Kotak Obat Pintar Berbasis Label Edukatif untuk Meningkatkan Kepatuhan Minum Obat saat Puasa pada Lansia di Kota Pekanbaru - Ratna Sari Dewi; Seftika Sari; Risa Zahra; Robiatul Adawiyah; Rozalifah Bella Syafitri; Salila Fitriah Zulfa; Shifa Khalisa Melza; Siti Zahara; Sri Amanda Jaya Aprilia; Tazkia Annafisah (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
Medication adherence among the elderly is an important factor in achieving successful therapy, particularly during the month of Ramadan when changes occur in meal patterns and medication schedules. Elderly patients with chronic diseases often experience difficulties in adjusting their medication timing, which may lead to poor adherence. This study aimed to implement a smart pill boxwith educational labels to improve knowledge and medication adherence among elderly individuals during fasting. The study involved 40 elderly respondents in a social care institution. The intervention consisted of training on the use of the smart pill box, educational labeling, and evaluation through observation, interviews, and checklist forms. The results showed that most respondents took medication twice daily (42.5%) and adjusted their medication schedules to sahur and iftar (45%). Before the intervention, 57.5% of respondents had not received information about medication use during fasting. The implementation of the smart pill boxwith educational labels improved the elderly’s understanding of medication use and supported better medication adherence during Ramadan.